2018
DOI: 10.31254/jmr.2018.4607
|View full text |Cite
|
Sign up to set email alerts
|

Public Health challenges associated with street-vended foods and medicines in a developing country: A mini-review

Abstract: The steady growth of urban population has necessitated the proliferation of wayside food and medicines vendors. These vendors include a large population of individuals with very little or no knowledge and training on basic food safety and drug matters. They are neither properly trained nor fully aware of the serious health dangers posed by microbial contamination of their wares. Therefore, from place of preparation to roadsides where the foods are sold, the chances of contamination by pathogens are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Most RTE foods (38.6%) were also stored at ambient temperatures. Temperature abuse by exposing food to ambient conditions encourages a wide range of spoilage and pathogenic microorganisms to proliferate causing infections and intoxications when the food is consumed (Obaji et al, 2018;Ouma et al, 2019;Shiningeni et al, 2019). Similar results were reported by Muhonja and Kimathi (2014) in Nakuru county, Kenya while assessing the hygiene and food handling practices among SFVs where cooked foods were stored at ambient temperatures exposed to the environment during sale which posed significant safety concerns.…”
Section: Storage and Preservation Practices Of Ready-to-eat Food By Street Food Vendorsmentioning
confidence: 56%
See 2 more Smart Citations
“…Most RTE foods (38.6%) were also stored at ambient temperatures. Temperature abuse by exposing food to ambient conditions encourages a wide range of spoilage and pathogenic microorganisms to proliferate causing infections and intoxications when the food is consumed (Obaji et al, 2018;Ouma et al, 2019;Shiningeni et al, 2019). Similar results were reported by Muhonja and Kimathi (2014) in Nakuru county, Kenya while assessing the hygiene and food handling practices among SFVs where cooked foods were stored at ambient temperatures exposed to the environment during sale which posed significant safety concerns.…”
Section: Storage and Preservation Practices Of Ready-to-eat Food By Street Food Vendorsmentioning
confidence: 56%
“…About 25.5% of the vendors indicated that they would consume the leftovers while 22.3% stored the foodstuffs without any form of preservation and sold them the following day. Leftover food can easily be contaminated by especially pathogenic microorganisms when stored under ambient temperatures posing safety concerns to the consumers (Obaji et al, 2018). This is worrying considering the poor handling and storage practices that the foods are exposed to during the day.…”
Section: Storage and Preservation Practices Of Ready-to-eat Food By Street Food Vendorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clearly observed that most samples packaged with nylon were free of fungal contaminants compared with samples packaged with banana leaves. Earlier studies had reported the presence of microbial contaminants in food products and medicines [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…capitata), carrot (Daucus carota), berries, mangos, star apples, onion (Allium cepa), tomatoes (Solanum lycopersicum), lettuce (Lactuca sativa) and green-pepper (Capsicum annuum). Fruits and vegetables are also prone to microbial contamination as they are constantly in contact with the environment (soil, animals droppings used as manure, water and dust, insect bites, etc) and during harvest and post-harvest handlings [6] [7]. Practices such as the use of untreated wastewater for irrigation and unhygienic post-harvest handling of the fruits and vegetables contribute to the contamination process.…”
Section: Introductionmentioning
confidence: 99%